Surface coating and characterisation of polyurea for liquid storage. Issue 8 (17th November 2017) - Arunkumar, T.; Ramachandran, S.
ABSTRACT: Compressed hydrogen fuel tanks were used for on-board hydrogen-fuelled vehicles which operate under high pressure and are subject to potential failures associated with pressure vessels. During a failure, hydrogen spills out through the cracks developed in these vessels. Organic materials are used to shield the leakage but mostly it fails due to improper surface and deposition of constituents of coating on the substrate. So in order to eliminate this potential threat a new approach was developed using polyurea coating as protective layer. It is very reactive and cures fast even at low temperature. In this investigation the polyurea coating was characterised using Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction. In addition to this, nuclear magnetic resonance was done on its binding components to confirm FTIR spectral results.